Beyond “Sharenting” a Cute Teething Baby Face: Maternal Agency in the Facebook Page of Ibuprofen-Based Analgesics for Children - Niquette, Manon (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
Teething is an ordeal for everyone in the family. Mothers are more likely than fathers to look for tips and ideas online for soothing a baby back to sleep. For this purpose, they are also more inclined to use social media that they can access through smartphone applications, such as Facebook. And because women are still the gateway to health-product sales, they are the primary target market for the advertising of pediatric drugs online, including teething pain-relief products. Recent studies have indicated that a large proportion of millennials believe that most marketing campaigns are not tailored to them. These women have trouble both identifying with the nuclear family as well as with recognizing themselves in the usual stereotypes. They find user-generated content more trustworthy and memorable than traditional brand-generated content. In this context, one may wonder how pharmaceutical companies have adapted their advertising discourse in social media in order to get the so-called digital women influencers to participate in the construction of the millennial caring mother. Drawing on recent works in the critical analysis of discourse, I deploy Michael Halliday’s systemic functional grammar, and more precisely the transitivity system and its processes, to study the content of a Facebook page dedicated to the promotion of over-the-counter ibuprofen-based analgesics for children. This allows me to identify how the emphasis that has been placed on the efficacy of drugs contributes to overshadowing the nightmarish labour that is necessary to care for a sick child.